تطبيق مؤشر جودة المياه (NSFWQI) على بحيرة نهر السن - رائد جعفر (Tishreen University, 2017)
يهدف البحث إلى تقييم جودة مياه بحيرة السن والتي تغذي بشكل أساسي مدينة اللاذقية وجزء من مدينة طرطوس لأغراض الشرب. قمنا في هذا البحث بدراسة مجموعة من العوامل الفيزيائية والكيميائية لمياه البحيرة خلال الأعوام التي توفرت فيها البيانات (1991-2004-2007-2011)، تم أخذ العينات من أربعة مواقع رصد مختلفة وفق البرنامج المعتمد من قبل المعنيين بمراقبة وحماية البحيرة وهي: (مأخذ اللاذقية، مأخذ طرطوس، مأخذ الري، مرصد النبع الجنوبي)، وقمنا بحساب مؤشر الجودة لأغراض الشرب باستعمال مؤشر المؤسسة الوطنية الأمريكية للصرف الصحي لجودة المياه National Sanitation Foundation Water Quality Index (NSFWQI). تم اعتماد تسعة عوامل: (الأوكسجين المنحل Dissolved Oxygen، تعداد العصيات الغائظية Fecal Coliform، الأس الهيدروجيني pH، الـ BOD5 Biochemical Oxygen Demand، درجة الحرارة Temperature، الفوسفات Phosphate، النترات Nitrates، العكارة Turbidity، المواد الصلبة الكلية Total Solids). بينت نتائج الدراسة أن تصنيف جودة المياه كانت جيدة في كافة نقاط الرصد الأربعة خلال الأعوام 1991 و2004 مع ملاحظة تحسن ملموس للجودة في العام 2004، وتنخفض بشكل بسيط خلال الأعوام 2007 و2011 لنقطتي الرصد في مأخذ اللاذقية ومأخذ الري ولكن تبقى ضمن حدود التصنيف الجيد، في حين تنخفض جودة هذه المياه لتدخل ضمن عتبة التصنيف الوسط لنقطتي الرصد مأخذ طرطوس ومرصد النبع الجنوبي. This research aims to evaluate the water quality of the Al-Sain lake which feeds mainly the Lattakia city and a part of the Tartous city of drinking water purpose. In this paper, we study a group of physical and chemical factors for the water of the Al-Sain lake during the years of available data (1991-2004-2007-2011), samples were taken from four different locations according to the program approved by the concerned staff to monitor and protect the lake, namely: (Lattakia water supply point, Tartous water supply point, irrigation point, southern spring observatory), and we calculated the quality index for drinking purposes using US approved methodology of National Sanitation Foundation. Nine factors have been adopted: (dissolved oxygen, fecal coliforms, pH, BOD5, temperature, phosphate, nitrates, turbidity, and total solids). The research result showed that the classification of water quality was good in all four monitoring points during the years 1991 and 2004, noting a significant improvement of the quality in 2004, and decreases slightly during the years 2007 and 2011 for monitoring points in the Lattakia water supply and irrigation points, but water quality still keep maintain a good classification, while the quality of the water goes down within the threshold of middle classification for the Tartous and southern spring observatory monitoring point.